A driving force, a driven force? Social media and police self-legitimacy - Czudnochowski, David (International journal of police science & management, 2023)
Social media (SM) have changed the conditions and forms of public communications and have been part of the standard communication repertoire of police authorities for a while now. Despite their importance, many aspects have been insufficiently researched, including their role in the self-legitimisation of the police. This article examines the SM strategies of police press and public relations in the context of an increasingly critical public in Germany. Based on expert interviews with press officers from German police authorities, it shows how police organisations are evaluating the changing communication landscape and which strategies they are pursuing to appear as legitimate authorities in an increasingly networked world. The focus is on how the police are adapting to the new technologies of SM and using them to negotiate legitimacy. We show how the police use SM to shape public debate, generate resonance and deal with the perceived loss of their interpretive authority. For this purpose, we question the self-image of the police as given by their media representatives. We examine it in discursive political struggles over crime and legitimacy. We show that social technological changes are turning the police into an active, opinion-forming actor who permanently have to negotiate their authority through visibility.